UMUR GLAS EEL (Anguilla spp.) YANG MASUK MUARA SUNGAI PROGO, YOGYAKARTA - Agung Budiharjo; Tjut Sugandawaty Djohan; Djumanto Djumanto; Jusup Subagja (The East Java Biological Society, 2009)
The leptocephalus drift with sea currents and moving from spawning area into coastal area near mouth of Progo River. In the coastal area, leptocephalus metamorfosed into glass eel, after that glass eel migrated to river. The aims of this research were to estimate glass eels age and predict hatching dates. Glass eels sampled on new moon during Februari 2007–Mei 2009 at mouth of Progo River. Glass eel ages estimated using their otolith microstructure. Hatching dates predicted with back calculation of glass eels age. We collected 1.082 glass eels. The ages of glass eel at recruit ranged from 58 to 190 days, and divided into 5 age groups. Glass eels are migrated to river hatched on “new moon” from July to January. Glass eels are migrated to river during October–January hatched during July–October. Glass eels are migrated to river during February–Juny hatched during November – January.